Evaluating Impact of Exchange Rate Fluctuation and Political Instability on Inflation: A Fresh Insight from Pakistan (Journal of Asian Development Studies, 2023)
Empirical research has been done to examine the impact of exchange rate fluctuations and political instability on inflation in Pakistan, using time series data spanning from 1990 to 2022. This study accounts for the contribution of both macroeconomic indicators and political factors towards inflation, taking Pakistan as a case study to depict that relationship. Unit root tests, co-integration, error correction model, and correlational analysis are applied. Findings suggest that there is a long-term relationship between selected macroeconomic and political variables contributing to the increased inflation in the country. The exchange rate is found to be marginally insignificant, and political instability and the presence of violence and terrorism are directly related to the increased inflationary trends in Pakistan. In contrast, the quality of government that includes political factors shows that a higher-quality government is likely to have better economic management policies and practices, which helps to control inflation and maintain price stability. Considering the results, it is suggested that if there is political stability in Pakistan, it will stabilize, which will lead to increased investment business confidence, and economic development.